The reliability of individualized load-velocity profiles - Banyard, H. G.; Nosaka, K.; Vernon, A. D.; Haff, G. G. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To examine the reliability of peak velocity (PV), mean propulsive velocity (MPV), and mean velocity (MV) in the development of load-velocity profiles (LVP) in the full-depth free-weight back squat performed with maximal concentric effort. Methods: Eighteen resistance-trained men performed a baseline 1-repetition maximum (1-RM) back-squat trial and 3 subsequent 1-RM trials used for reliability analyses, with 48-h intervals between trials. 1-RM trials comprised lifts from 6 relative loads including 20%, 40%, 60%, 80%, 90%, and 100% 1-RM. Individualized LVPs for PV, MPV, or MV were derived from loads that were highly reliable based on the following criteria: intraclass correlation coefficient (ICC)>.70, coefficient of variation (CV)=10%, and Cohen d effect size (ES)<0.60. Results: PV was highly reliable at all 6 loads. MPV and MV were highly reliable at 20%, 40%, 60%, 80%, and 90% but not 100% 1-RM (MPV: ICC=.66, CV=18.0%, ES=0.10, SEM=0.04 m/s; MV: ICC=.55, CV=19.4%, ES=0.08, SEM=0.04 m/s). When considering the reliable ranges, almost perfect correlations were observed for LVPs derived from PV20-100% (r=.91-.93), MPV20-90% (r=.92-.94), and MV20-90% (r=.94-.95). Furthermore, the LVPs were not significantly different (P>.05) between trials or movement velocities or between linear regression versus 2nd-order polynomial fits. Conclusions: PV20-100%, MPV20-90%, and MV20-90% are reliable and can be utilized to develop LVPs using linear regression. Conceptually, LVPs can be used to monitor changes in movement velocity and employed as a method for adjusting sessional training loads according to daily readiness.